IMPACT OF STRESS MULTI-AXIAL EFFECT ON 316 STAINLESS STEEL CREEP DESIGN MARGIN - SHEN XiaoPeng; XUAN FuZhen (Jixie qiangdu)
ASME NH high-temperature design code put limits on inelastic strain. However,there are several arguments about this provision. For instance,the multi-axial effect and different design margins for different materials were not considered.In this paper,a 316 stainless steel 90°elbow at 550℃ was simulated to study impact of multi-axial effect on creep design strain margin. A continuum damage constitutive model was used,also new damage variables were defined based on multi-axial creep ductility theory. These damage variables were investigated when strains of the elbow reached corresponding limits in order to judge whether ASME NH strain limits are conservative. It is shown that all the damage variables are well below unity when the membrane strain of the elbow reaches the strain limits of 1%. It is thus concluded that ASME NH strain limits is still conservative when multi-axial effect is considered in a 316 stainless steel structure and can be used for design and verification at this temperature.